1991
DOI: 10.1128/jvi.65.5.2220-2224.1991
|View full text |Cite
|
Sign up to set email alerts
|

Construction and properties of retrovirus packaging cells based on gibbon ape leukemia virus

Abstract: We have constructed hybrid retrovirus packaging cell lines that express the gibbon ape leukemia virus env and the Moloney murine leukemia virus gag-pol proteins. These cells were used to produce a retrovirus vector at over 106 CFU/ml, with a host range that included rat, hamster, bovine, cat, dog, monkey, and human cells. The gag-pol and env expression plasmids were separately transfected to reduce the potential for helper virus production, which was not observed. The NIH 3T3 mouse cells from which the packagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
163
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(165 citation statements)
references
References 27 publications
0
163
1
1
Order By: Relevance
“…The ability of these domains to independently regulate cytokine production in primary, human lung fibroblasts was examined. The full-length human CD40ct, the first 35 amino acids of the CD40ct encompassing the TRAF6 binding sites (1-35), and amino acids 35-53 containing the TRAF2/TRAF3 binding domain were expressed in L828 fibroblasts as fusion proteins with the extracellular domain of human CD8 by retroviral transduction [25,26]. Typically 40-80% of L828 fibroblasts expressed CD8 2-3 days post infection, while mock-infected L828 fibroblasts did not express CD8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of these domains to independently regulate cytokine production in primary, human lung fibroblasts was examined. The full-length human CD40ct, the first 35 amino acids of the CD40ct encompassing the TRAF6 binding sites (1-35), and amino acids 35-53 containing the TRAF2/TRAF3 binding domain were expressed in L828 fibroblasts as fusion proteins with the extracellular domain of human CD8 by retroviral transduction [25,26]. Typically 40-80% of L828 fibroblasts expressed CD8 2-3 days post infection, while mock-infected L828 fibroblasts did not express CD8 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the GFP-1 gene from pEGFP-1 (Clontech, Palo Alto, CA) was cloned into the pJM573neo retroviral vector (30,31). Vector supernatants containing different pseudotyped vector particles were generated using the gibbon ape leukemia virus envelope containing the PG13 packaging cell line (32). Retroviral supernatants containing the GFP vector were produced as follows: plasmid pOT24 was transfected into GP&E86 ecotropic producer cells (American Type Culture Collection [ATCC] CRL-9642) (33) using DOTAP (Boehringer-Mannheim, Indianapolis, IN) as directed by the manufacturer.…”
Section: Retroviral Vector Construction and Virus Productionmentioning
confidence: 99%
“…packaging cell lines including PG-13 (GaLV-pseudotype), GPþE-86 (murine ecotropic), and PA317 (murine amphotropic) were derived from NIH 3T3 cells (Markowitz et al, 1988;Miller and Buttimore, 1986;Miller et al, 1991), whose lysate was found to enhance transduction by 1.4-to 2.7-fold. The VCM is often stored frozen prior to the transduction process.…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral vectors with a humanized red-shifted green fluorescent protein (GFP) reporter gene under the control of MSCV long terminal repeats were produced from a PG-13 packaging cell line (GaLV, TFL;Hennemann et al, 1999;Miller et al, 1991) or a GPþE-86 packaging cell line (ecotropic, TFL; Buske et al, 2001;Markowitz et al, 1988). Both cell lines were cultured in DMEM with 10% FBS in 1,700 cm 2 expanded surface roller bottles (Corning, Lowell, MA) at 378C and 10% CO 2 in air.…”
Section: Cell Lines and Retroviral Vector Productionmentioning
confidence: 99%